Personality Styles of German-Speaking Psychotherapists Differ from a Norm, and Male Psychotherapists Differ from Their Female Colleagues - Peter, Burkhard; Böbel, Eva; Hagl, Maria; Richter, Mario; Kazén, Miguel (Frontiers in Psychology, 2017)
The “therapist variable”, that is, variables pertaining to the person of the psychotherapist, has been neglected in psychotherapy research for some time. Therapist characteristics in general have been shown to influence the working alliance and psychotherapeutic outcome. Concerning personality in particular, however, research has mostly focused on its relation with the therapist’s choice of method, or differences between the various major therapy approaches without specifying how exactly psychotherapists are in comparison to other people. We wanted to know: Are there specific personality styles that distinguish psychotherapists from the norm? A sample of 1,027 psychotherapists from Germany, Austria, and Switzerland filled out the short version of the Personality Style and Disorder Inventory (PSDI-S) via online survey. The PSDI-S is a self-report questionnaire that assesses 14 personality styles, partly related to the non-pathological equivalents of classifiable personality disorders. The psychotherapists were compared to a normative sample of 3,392 people of different professions. The results could be divided into three groups: (1) Large differences in four personality styles that might contribute to relationship competencies and may enable psychotherapists to put their own personal opinion aside, show empathy and appreciation, open themselves to the emotional experience of the patient, and provide a trusting relationship. (2) Moderate differences in seven personality styles that are equally indicative of the professional social skills of the psychotherapists, i.e. they were neither submissive nor passive, not excessively helpful, but also not too self-assertive. (3) Hardly any or no differences regarding a charming (histrionic) style, optimism, and conscientiousness. Gender-specific results revealed that male psychotherapists differed from their female colleagues, but they did so differently than men and women in the normative sample do. The main limitations were that we relied on self-report and did not statistically control for gender, age, and education, when comparing to the norm. As a conclusion, German-speaking psychotherapists appear to show quite functional personality styles but this needs corroboration from studies that use different methods and measures.